2013
DOI: 10.1002/hlca.201200224
|View full text |Cite
|
Sign up to set email alerts
|

Doped Nano‐Sized Copper(I) Oxide (Cu2O) on MelamineFormaldehyde Resin: a Highly Efficient Heterogeneous Nano Catalyst for ‘Click’ Synthesis of Some Novel 1H‐1,2,3‐Triazole Derivatives Having Antibacterial Activity

Abstract: A facile and simple protocol for the 1,3‐dipolar cycloaddition of organic azides with terminal alkynes catalyzed by doped nano‐sized Cu2O on melamineformaldehyde resin (nano‐Cu2OMFR) as a new and convenient heterogeneous catalyst is described. In this method, ‘click’ cycloaddition of various structurally diverse β‐azido alcohols and alkynes in the presence of nano‐Cu2OMFR in H2O/THF 1 : 2 furnished the corresponding 1,4‐disubstituted 1H‐1,2,3‐triazole adducts 1a–1o in good to excellent yields at room temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Hence, MF, doped with e.g. copper(I) oxide, can be a convenient heterogeneous catalyst . Highly porous MF resins have also been suggested for adsorption of pollutants but do also have very interesting CO 2 adsorption properties .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, MF, doped with e.g. copper(I) oxide, can be a convenient heterogeneous catalyst . Highly porous MF resins have also been suggested for adsorption of pollutants but do also have very interesting CO 2 adsorption properties .…”
Section: Introductionmentioning
confidence: 99%
“…Applying Cu 2 O powder directly in a title reaction usually results an incomplete conversion and also require long reaction time 16 . Efforts have also been made to enhance the catalytic efficiency of Cu 2 O 17 18 19 20 . It is reported that 17 polyvinylpyrrolidone-coated Cu 2 O nanoparticles can act as an efficient catalyst for cycloaddition reactions in water at physiological temperature.…”
mentioning
confidence: 99%
“…12), with a diameter of approximately 25 nm and evaluated its catalytic activity in the copper-catalyzed azide-alkyne cycloaddition (CuAAC) reaction (Scheme 17, Table 17, Method A). 51 Nano copper-doped silica cuprous sulfate (CDSCS), proved also to be a highly efficient heterogeneous catalyst for the regioselective synthesis of 1,4-disubstituted 1,2,3-triazoles derivatives 41g and 41ah-bj. 50 Rad et al reported that the 1,3-dipolar cycloaddition of organic azides with terminal alkynes 35 can be catalyzed by doped nano-sized Cu 2 O on melamine formaldehyde resin (nano-Cu 2 O MFR) to furnish the corresponding 1,4-disubstituted 1H-1,2,3-triazole adducts 41s-ag in good to excellent yields at room temperature (Scheme 17, Table 17, Method B).…”
Section: Scheme 16mentioning
confidence: 99%